2022
DOI: 10.3389/fimmu.2022.947341
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose IL-2 improved clinical symptoms by restoring reduced regulatory T cells in patients with refractory rheumatoid arthritis: A randomized controlled trial

Abstract: BackgroundRegulatory T cells (Tregs) have been found to play crucial roles in immune tolerance. However, the status of Tregs in refractory rheumatoid arthritis (RA) is still unclear. Moreover, low-dose interleukin-2 (IL-2) has been reported to selectively promote the expansion of Tregs. This study investigated the status of CD4+ Tregs and low-dose IL-2 therapy in patients with refractory RA.MethodsThe absolute number of CD4+CD25+FOXP3+ Treg (CD4 Treg), CD4+IL17+ T (Th17), and other subsets in peripheral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…We have previously reported that Tregs are significantly reduced with the aggravation of disease in RA patients, and combined with low-dose IL-2 therapy can maintain or even rebuild autoimmune homeostasis by promoting the proliferation of Treg cells, thus delaying the deterioration of disease ( 22 , 30 ). Great heterogeneity exists in the clinical presentation and immune mechanisms of RA, as a consequence, not all patients respond similarly to the same drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that Tregs are significantly reduced with the aggravation of disease in RA patients, and combined with low-dose IL-2 therapy can maintain or even rebuild autoimmune homeostasis by promoting the proliferation of Treg cells, thus delaying the deterioration of disease ( 22 , 30 ). Great heterogeneity exists in the clinical presentation and immune mechanisms of RA, as a consequence, not all patients respond similarly to the same drug.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that combined with low-dose IL-2[0.5 Million International Units (MIU)/day of IL-2 for five consecutive days] on the basis of previous treatment can promote the proliferation of circulating Tregs in patients with RA, PsA, and pSS, and significantly improve the symptoms of patients ( 22 , 28 , 29 ). Therefore, eligible participants were randomly assigned to three age-sex matched groups: control group (n=15), IL-2 group (n=26), and IL-2+TCZ group (n=9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also demonstrated that during the course of their study, there was no significant decrease in rheumatoid factor (RF) and anti-cyclic-citrullinated peptide (anti-CCP) [ 19 ]. Wang et al demonstrated that patients who received low-dose IL2 therapy in conjunction with conventional therapy had a greater clinical response with a significant decrease in the DAS28 score, 28 tender count, and swollen joint count as compared with RA patients being treated with only conventional therapy [ 20 ]. The findings in this study consolidated the findings of the study carried out by Zhang et al, which suggested that the significant improvement seen in the low-dose IL2 group is directly correlated with immunomodulation.…”
Section: Reviewmentioning
confidence: 99%
“…Severe adverse effects in the study were noted to be singular events and no specific association was seen with treatment [ 19 ]. Wang et al also conducted a randomized controlled trial in which they demonstrated that other than mild reactions at the injection sites in some patients treated with low-dose IL2, no other adverse effects were noted [ 20 ]. Similarly, Zhang et al conducted a non-randomized clinical trial where RA patients were given low-dose IL2 therapy in conjunction with conventional therapy and were followed after five days of treatment regimen [ 21 ].…”
Section: Reviewmentioning
confidence: 99%